QUALITATIVE ANALYSIS OF FACTORS AFFECTING TAX COMPLIANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Rakhmawati, Intan; BS, Raden Sapto Hendri; Tusta Citta Ihtisan Tri Prasidya (Jurnal Riset Akuntansi, 2024)
Tax as main source of revenue state. With the number of MSME’s crucial in all regions, including Mataram City, tax revenue needs to be analyzed in terms of tax payment compliance. In 2018, tax revenue from MSME’s (Micro, Small, and Medium Enterprises) was only IDR 5.7 trillion, from a total tax revenue of IDR 1,472 trillion. The application used for payment and reporting is relatively easy, but an evaluation of why tax payment and reporting compliance from MSME’s is still low needs to be analyzed. This research uses a descriptive method. The research method with documentation, questionnaires, and interviews. The results show that the digitalization variable and the simplification of tax regulations are have no effect on taxpayer compliance, both for tax payments and reporting. MSME’s argue that tax digitalization has not been fully implemented, so it hasn’t been able to boost taxpayer compliance. In addition, tax regulations are not entirely simple, to be calculated by MSME’s, because the education background of managers is generally not from economics. As a suggestion, the expansion of the types of informants and types of tax applications/systems evaluated needs to be improved, to prove whether the Digital Empowerment theory applies or not in Indonesia.